REVIEW OF THE MONOGRAPH “DIETARY CULTURE OF THE PEOPLES OF DAGESTAN IN XIX – EARLY XXI CENTURIES” BY Z.B. RAMAZANOVA. - Sulejmanova, Sevda Alievna (History, Archeology and Ethnography of the Caucasus, 2019)
Food occupies a significant place in life of any ethnic group and is one of the main sources for studying not only the peoples’ history, but also the functioning mechanism of cultural heritage in current context. Nutritional preferences reflect ethnical and social history, as well as specifics of historical and cultural contacts. The study of local variants of Dagestan peoples’ diet in the context of transformations of public and household life on the one hand, and ethnocultural contacts on the other, is covered in Z.B. Ramazanova’s monograph, entitled “Dietary culture of the peoples of Dagestan in XIX – early XXI centuries”. It examines ethnical features of eating habits among rural population of Dagestan, main components of traditional diet resulting from natural geographical factors and household activities.